Venous Thromboembolism Prophylaxis in Plastic Surgery Patients Undergoing Facelift. (12th April 2022) - Gupta, Rohun; John, Jithin; Gupta, Monik; Shaheen, Kenneth
Abstract: Background: In 2011, the American Society of Plastic Surgeons approved the Venous Thromboembolism (VTE) Task Force Report, which recommended the use of the Caprini scoring system, which has been adopted for VTE prophylaxis by most surgical societies in America. Objectives: The aim of this study is to investigate the incidence of deep vein thrombosis (DVT) and pulmonary embolism (PE) in patients undergoing facelifts at a single institution who did not undergo VTE chemoprophylaxis based on the Caprini scoring system. Methods: A retrospective chart review was conducted of patients who underwent facelift at a single institution. Patients were included if they were operated on between 2016 and 2021 by the lead surgeon and excluded if they received VTE prophylaxis. Descriptive statistics were conducted to analyze the collected data. Results: In total, 136 patients were isolated after chart review, and no patients were found to have had DVT or VTE. The average Caprini score was 5.625 and ranged from 3 to 10. There were 3 patients with evidence of postoperative hematoma (Caprini score = 5, 5, 7). The overall hematoma percentage was 2.21%. Conclusions: Based on the average Caprini score for the patients, all patients should have received VTE chemoprophylaxis. The authors found no VTE-related events in the patients without chemoprophylaxis. This study suggests that while the Caprini scoring system is a critical diagnostic tool for certain surgical procedures, it might not be optimal in predicting VTE in aesthetic patients undergoing surgical procedures. Level of Evidence: 4: